Terpenoid composition and botanical affinity of Cretaceous resins from India and Myanmar - Dutta, S.; Mallick, M.; Kumar, K.; Mann, U.; Greenwood, Paul (2011)
Fossil resins from the Cretaceous sediments of Meghalaya, India and Kachin, Myanmar (Burma) were analysed using Curie point pyrolysis-gas chromatography-mass spectrometry and thermochemolysis gas chromatography-mass spectrometry to help elucidate their botanical source. The major pyrolysis products and methyl-esterified thermochemolysis products of both the resins were abietane and labdane type diterpenoids with minor amount of sesquiterpenoids. The thermochemolysis products also included methyl-16,17-dinor callitrisate, methyl-16,17-dinor dehydroabietate and methyl-8-pimaren-18-oate-the latter two from just the Myanmarese resin. The exclusive presence of both labdane and abietane diterpenoids and the lack of phenolic terpenoids may suggest that the studied Cretaceous resins were derived from Pinaceae (pine family) conifers. © 2010 Elsevier B.V.